Leisure activities among the Zoroastrians elderly in Kerman, Iran / Abdolhossein Daneshvarinasab - Abdolhossein, Daneshvarinasab (2016)
The problem of this study was that how the Zoroastrians’ elderly in Kerman, Iran spend their outdoor leisure time, and what was contribution of leisure activities to religious continuity among them. Based on this problem, the main goal of this study was to explore the leisure activities among the Zoroastrians’ elderly in Kerman, Iran. For this aim, outdoor leisure activities’ patterns, outdoor leisure preferences, and the factors which affect their outdoor leisure activities were examined. In addition, this study explored the perceived leisure constraint among the Zoroastrians’ elderly in order to identify the factors which constraint their leisure preferences and real participation. The study also attempted to explore the contribution of leisure activities to religious continuity among the Zoroastrians’ community in Iran. Using anthropological methods such as participant observation, in-depth interview, and anthropological photography, data were collected during the fieldwork among the Zoroastrians’ elderly from September 2010 to September 2012. As an ethnographer, the researcher took part in their everyday leisure activities in order to gain deep understanding of their leisure through the meaning which they ascribed to their experiences. The purposive sampling technique were adopted to select the informants of the study. Depending on the informants’ scope of the experiences and understating, the process of sampling continued till no new data turned up during data collection process (data saturation). Finding of the study revealed that the most leisure activities among the Zoroastrians were speculative and cultural activities, social activities, and physical activities. Regarding the leisure companions, informants spent their leisure time with family members, friends, respectively, only a few percent of them alone. This distribution depends on the gender of the informants where female elders preferred to spend their leisure time mainly with family, while male elders have shown more tendency to spend their leisure time with friends. The effect of the economic status on the type and quality of use of leisure time and access to leisure facilities is supported in this study. Based on the finding of the study, leisure constraints of the informants were classified into three categories: intrapersonal, interpersonal, and structural. During the past two decades, Zoroastrians have come up with some strategies to solve the problem of identity which has been occurred due to low birth rate and immigration to overseas among the Zoroastrians. Most of these strategies involved the simplification of religious rituals and festivals so that most of these rituals could be performed in the form of leisure. This simplification process is then called holy leisure. The purpose of this process is to attract more Zoroastrians especially ordinary people to this religion. Sanctification and desanctification are dichotomies which have played a fundamental role in the generation and regeneration of Zoroastrians’ identity residing in Iran and continuation of their religion.